Studies on Phytoplanktonic Diversity in Relation to Physicochemical Parameters and Palmer's Pollution Index in Khairan Stream: A Case Study from Shivalik Ranges, Kangra, Himachal Pradesh, India - Sharma, Shivali; Banyal, Harinder Singh (Indian Forester, 2025)
The present research article deals with study of phytoplankton diversity in relation to physicochemical parameters of the Khairan stream, a tributary of Beas River in Shivalik ranges of Kangra district, Himachal Pradesh, India. Total of 27 genera of phytoplankton were recorded, out of which 14 genera belongs to Bacillariophyceae, 11 genera belongs to Chlorophyceae, while remaining 2 genera belongs to Cyanophyceae. One-way ANOVA analysis shows that there is significant difference in plankton diversity with respect to seasons (F, 3.39>Fcrit, 2.44). Pearson's correlation coefficient analysis was used to assess the correlation between various physicochemical parameters and phytoplankton assemblage. Additionally, Palmer's Pollution Index (PPI) was used to evaluate the overall pollution status of the stream. The calculated PPI values indicates that there is high pollution level in the stream during summer (20) due to low water level, followed by winter (18), spring (16), monsoon (10) and autumn (5), so proper conservation strategies are needed to preserve the native biodiversity especially fishes of said water body.